Analisis SWOT dan Critical Success Factor pada Sistem Informasi Logistik IGD Berbasis Google Workspace - Ganef Tri Wijayatno; Fahreza Dandy Sihmawanto; Prind Triajeng Pungkasanti (Bulletin of Computer Science Research, 2025)
The Emergency Department (ED) Logistics Information System (IGD) is a crucial element in ensuring the smooth distribution of medical supplies, thus maintaining the quality of healthcare services. Utilizing cloud-based services such as Google Workspace offers an innovative solution for integrating various logistics functions into one platform, from stock management to real-time reporting. This study aims to evaluate the internal and external conditions of the Google Workspace-based ED Logistics Information System using a SWOT approach and to determine Critical Success Factors (CSFs) as the basis for development strategies. The research method used quantitative and qualitative descriptive analysis. Based on observations, questionnaires, and interviews with ED logistics staff, nurses, and management directly involved in system management, the IFAS analysis showed that the total score for weaknesses (0.75) was slightly higher than the strengths (0.73), indicating persistent internal constraints, particularly in data security, limited specific logistics features, and reliance on internet connectivity. Meanwhile, the EFAS analysis showed that external threats (0.75) outweighed opportunities (0.74), with the primary threats being dependence on third parties, the risk of data breaches, and staff resistance to the new system. The CSF analysis identified that system success is influenced by improved data security, the development of specialized logistics features, and ongoing management support. The results of this study are expected to serve as a reference in developing strategies to improve the effectiveness and reliability of cloud computing-based emergency room logistics systems.